The Health Education of Narkolema for Adolescents In Wonorejo Karanganyar - Hardiningsih hardiningsih; Fresthy Astrika Yunita; Agus Eka Nurma Yuneta (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Introduction: The existence of communication media and the development of technology, communication, and information that increase rapidly made it easier to spreading pornography content. A survey stated that every year, there are 72 million visitors to a pornography website. Every second, 28.000 internet users see pornography content. Two-third pornography consumers on the internet are men and the rest are women. Group of age 12-17 years old are the biggest pornography consumer on the internet. Narkolema (Drugs Through The Eye) is pornography that was seen by someone that have addictive effect and damage potential just as junkies. The damage that was suffered because of pornography addiction is the damage of the prefrontal cortex (PFC). The prefrontal cortex is functioned as consideration and decision making central and as personality former.Purpose: To give the extension for adolescents about narkolema so they will know about narkolema.Extension Method: Held a lecture for adolescents about narkolema by first held a pretest, then after the extension had done, the posttest was held to know the effect from the given extension.Extension Result: The extension about narkolema for adolescents was held by first held a pretest, then the posttest was held after the extension. There was an increase in the adolescents’ knowledge about narkolema.Conclusion: There was a positive effect of the extension of narkolema toward the adolescents’ knowledge of narkolema.